Expression Profile of Circular RNAs in Oral Squamous Cell Carcinoma - Shao, Yanxiong; Song, Yuhan; Xu, Siming; Li, Siyi; Zhou, Haiwen (Frontiers in Oncology, 2020)
Background Circular RNAs (circRNAs) are involved in the pathogenesis of several diseases. Among oral maxillofacial cancers, oral squamous cell carcinoma (OSCC) has the highest incidence. However, the role of circRNAs in OSCC is still not clear. The aim of our study was to evaluate the circRNA expression profile in OSCC and explore further the potential role of circRNAs in the pathogenesis of OSCC. Methods CircRNA sequencing was performed in 6 pairs of samples of OSCC and normal oral mucosal tissues. Expression of selected circRNAs was validated by qRT-PCR. GO and KEGG analyses were performed and binding relationships between circRNAs and miRNAs were predicted. The hsa_circ_0001766/miR-877-3p/VEGFA axis was selected to further elucidate its role in OSCC. Results We showed that there were 122 differentially expressed (DE) circRNAs. Eight out of 10 selected circRNAs were validated by qRT-PCR. GO and KEGG analyses indicated that the identified DE circRNAs might be involved in the progression of OSCC. Then, after identification by Sanger sequencing and RNase R assay, the upregulated hsa_circ_0001766 was selected to investigate its potential role in OSCC. Bioinformatics analysis showed that hsa_circ_0001766 might act as a competing endogenous RNA (ceRNA) that sponged miR-877-3p to upregulate VEGFA expression. We selected OSCC cell lines SCC9 and SCC25. PCR results showed that the expression of hsa_circ_0001766 and VEGFA was upregulated in SCC9 and SCC25. Subsequently, using western blot, PCR, CCK8, and colony formation assays, we found that knocking down circRNA0001766 inhibited the expression of VEGFA and the proliferation of OSCC cells. Following this, miR-877-3p inhibitor reversed the inhibitory effect of si-hsa_circ_0001766 on expression of VEGFA and proliferation of OSCC cells. Conclusions In conclusion, our study revealed the possible role of circRNAs in the pathogenesis of OSCC, and identified the potential role of the hsa_circ_0001766/miR-877-3p/VEGFA axis in OSCC progression.